Technika dávkovania jemnej suspenzie v atómovej spektrometrii - Kriegerová, Katarína; Procházková, Simona; Halko, Radoslav (Chemické listy, 2019)
This review presents a recent developments and appli-cations of the slurry sampling (SS) as an approach for the minimization of sample preparation prior to the analysis of solid samples by atomic spectrometry. The paper is fo-cused on the description of the basic critic factors of SS. Some advantages or drawbacks of this technique are also discussed. At the end, the applications of combined SS and atomic spectrometry for the determination of metals in various solid matrices (environmental, biological, food and others) are presented.